Experimental investigation of the effect of nano fluid use on heat transfer in unmanned aircraft cooling system with different types of wing geometry - Gunes, Abdulsamed; Erdogan, Beytullah; Cakmak, Gulsah (Elsevier - Division Reed Elsevier India Pvt Ltd, 2025)
Unmanned aerial vehicles (UAVs) have performed critical tasks such as air dominance, national security, wildlife surveillance, damage detection studies after natural disasters, early intervention in forest fires, management activities, explosions, and logistics. UAVs, which perform these critical tasks and whose importance has been increasing in the world in recent years, experience a loss of thermal efficiency in their cooling systems at critical times during flight. In order to optimize cooling mechanisms for UAVs, this study aims to redesign existing cooling fins. In addition, it is planned to use nanofluids instead of traditional coolants in these radiators. In addition to the increased cooling performance with the use of nanofluid, it has been determined that this effect is further increased by the use of new design parts (Radiator-F1, Radiator-F2, Radiator-F3) consisting of louver type fin structures with different fin geometries in number and pattern compared to standard flat fins (Radiator-S). In these newly designed cooling systems were tested at flow rates of 20 and 22 lt/min, a temperature of 70 degrees C, and an inlet pressure of 0.2 bar are focused on increasing the cooling efficiency of the coolers. Experiments were carried out on standard and newly designed radiators using Al2O3, ZnO and CuO nanofluids at 0.3 % volumetric concentration for thermal performance measurement. The heat transfer in Radiator-S using pure water was calculated as 9.02 kW. The heat transfer amount in the newly designed Radiator-F1 using pure water was the highest and increased by approximately 23 %. The heat transfer increase in Radiator-F1 using CuO nanofluid was the highest and was determined to be approximately 38 % compared to using pure water in Radiator-S. Thermal conductivity and viscosity ratios increased compared to pure water. The highest increase in thermal conductivity was approx 18 % in ZnO nanofluid and viscosity was approx 16 % in Al2O3 nanofluid. The improvement resulting from the findings increases the operational capabilities of the (UAVs). In addition, the lightness resulting from a more compact system indirectly increases the flight duration. These results demonstrate significant improvements in cooling performance for UAV applications.
Keywords: Unmanned aerial vehicle; Nanofluid; Radiator; Cooling; Coolant